2006
DOI: 10.1002/hyp.6080
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties in DRAINMOD predictions of subsurface drain flow for an Indiana silt loam using the GLUE methodology

Abstract: Abstract:Good modelling practice requires the incorporation of uncertainty analysis into hydrologic/water quality models. The generalized likelihood uncertainty estimation procedure was used to evaluate the uncertainty in DRAINMOD predictions of daily, monthly, and yearly subsurface drain flow. A variance-based sensitivity analysis technique, the extended Fourier amplitude sensitivity test, was used to identify the main sources of prediction uncertainty. The analysis was conducted for the experimental drainage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 45 publications
(59 reference statements)
1
23
0
Order By: Relevance
“…For example, the total effects of the antecedent centres c m in the performance of TSK2.5 are generally low, but the statistic REP (reflecting the relative error to the peak) was found to be very sensitivity to these parameters in the case of the seasonal catchments. These results are in agreement with previous research, showing that the sensitivity of the parameters of a rainfall-runoff model is dependent on the catchment's hydroclimatic characteristics and on the measure of model performance (Tang et al, 2007;van Werkhoven et al, 2008). However, broad generalizations on parameter sensitivities of the fuzzy models TSK1.5 and TSK2.5 can still be attempted, with the purpose of facilitating the calibration process by identifying the parameters with the highest influence in the model's goodness of fit, and those which can be fixed without important loss of accuracy in the discharge estimates.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…For example, the total effects of the antecedent centres c m in the performance of TSK2.5 are generally low, but the statistic REP (reflecting the relative error to the peak) was found to be very sensitivity to these parameters in the case of the seasonal catchments. These results are in agreement with previous research, showing that the sensitivity of the parameters of a rainfall-runoff model is dependent on the catchment's hydroclimatic characteristics and on the measure of model performance (Tang et al, 2007;van Werkhoven et al, 2008). However, broad generalizations on parameter sensitivities of the fuzzy models TSK1.5 and TSK2.5 can still be attempted, with the purpose of facilitating the calibration process by identifying the parameters with the highest influence in the model's goodness of fit, and those which can be fixed without important loss of accuracy in the discharge estimates.…”
Section: Discussionsupporting
confidence: 92%
“…Francos et al, 2003;Kanso et al, 2005;Wang et al, 2006;Ratto et al, 2007;Tang et al, 2007). SVD has the advantage over RSA of being able to deal with all kinds of parameter interactions in the model structure.…”
Section: Sobol's Variance Decompositionmentioning
confidence: 99%
“…Generally, the median of the CDF based on the rescaled likelihood measures, represents the deterministic model prediction, and the uncertainty bound can be represented with the 90% confidence interval bounded by 5% and 95% confidence levels [55][56][57]. In this study, the behavioral model is based on a cut-off threshold, by taking the top 30% of likelihood measures [58], and is used to estimate 90% of uncertainty bounds for approximation of a flood discharge.…”
Section: Approximation Of Flood Discharge Using the Glue Methodologymentioning
confidence: 99%
“…DRAINMOD calculates drainage rates assuming that lateral water movement occurs mainly in the saturated region, which usually contains the drains, where LK s significantly affects all the drainage functions. Sensitivity analyses conducted on DRAINMOD show that it is very sensitive to changes in LK s (Haan and Skaggs, 2003; Wang et al , 2006). A previous study by Salazar et al (2008) showed that LK s values required by DRAINMOD can be estimated from ROSETTA‐predicted K s values, with LK s values being up to four times K s values.…”
Section: Methodsmentioning
confidence: 99%